Allelopathic Effects of Bark and Stem of Trees and Weeds Species on Morpho-agronomic Traits of Wheat: Allelopathic Effects of Bark and Stem of Trees - Muhammad Azhar Khan; Zaffar Iqbal; Manzoor Hussain; Ghulam Mujtaba Shah; Aftab Afzal; Abida Bibi; Adeela Bibi; Rabia Afza; Muhammad Sajid (Biological Sciences - PJSIR, 2023)
Potential weeds in wheat field and trees growing on borders of small land holdings are threatening to wheat growth and yield. A field experiment was conducted to evaluate the phytotoxic potentials of stem and barks of different weeds and trees that are switch sorrel (Dodonaea viscosa L), river red gum (Eucalyptus camaldulensis L.), earth smoke (Fumaria indica L.), walnut (Juglans regia L.), athel tree (Tamarix indica Willd. ), dandelion (Taraxacum campylodes L.), Indian olive (Olea ferruginea Royle.) on morpho-agronomic traits of wheat (Triticum aestivum),cultivar Pirsabaq 2005. 500 g stem dry powder of each allelopathic plant was applied on wheat. The result revealed that all the treatments showed significantly inhibitory effects. Within treatments Eucalyptus camaldulensis has maximum allelopathic effect on plant height (61.63cm), while minimum effect was observed in Juglans regia treatment (69.95cm). Similarly, Eucalyptus camaldulensis showed maximum allelopathic effect on length of internodes (15.84cm) and length of spike (7.17cm), while Olea ferruginea Royle and Taraxacum campylodes showed minimum effect on these two parameters espectively. Maximum number of grains per spike and weight of 100 grain were observed with Taraxacum campylodes and Juglan regia treatments, while minimum number of spikelet per spike and weight of 100 grain were found in Eucalyptus camaldulensis and Olea ferruginea Royle treatments respectively. Maximum grain yield was found in Taraxacum campylodes treatment (21.67g).The results pointed out that bark of Eucalyptus camaldulensis has highest phytotoxic effect while stem of Taraxacum campylodes has minimum effect. Eucalyptus camaldulensis should not planted near agricultural field of wheat, while Taraxacum campylodes residues should be left in field which can none toxic for wheat.